PEACE OPERATIONS: NEW MANDATES AND THEIR IMPLICATIONS FOR TROOPS CONTRIBUTING COUNTRIES - Cruz Aguilar, Sergio Luiz [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2015)
The article presents the changes in contemporary peacekeeping operations conducted by the United Nations (UN) in a historical perspective and its implications for the troops contributing countries. Based on literature of the subject and UN documents the text presents the conceptual and legal support for the implementation of these operations and describes the evolution of mandates and the use of force by the military component. Based on recent changes, we discuss trends in the approval and conduct of operations and their implications for the troops contributing countries.
Keywords: Peace Operations; United Nations; International Security